The role of online customer reviews in mediating live streaming and price on purchasing decisions for Somethinc products on TikTok Shop - Mardiananta, Jerry; Nurfarida, Iva Nurdiana; Suroso, Adi (JURNAL MANAJEMEN MOTIVASI, 2025)
This study aims to investigate the role of online customer reviews as a mediator of the impact of live streaming and price on Tiktok shop consumers’ purchasing decision for Somethinc product. This study is based on the phenomenon occurring on TikTok Shop regarding consumer purchasing decisions for skincare products, which are now highly competitive. In this study, an online Likert scale survey serves as the method of data collecting. The sample consists of 100 respondents, who are consumers who have purchased Somethinc products on TikTok Shop. The analysis tool employed PLS-SEM, utilizing the SmartPLS 3.0 program for assistance. The results of the study show that (1) live streaming has a significant influence on purchasing decisions, whereas price does not have a significant influence. (2) Online customer reviews do not have a significant influence on purchasing decisions. (3) Live streaming and price have a significant influence on online customer reviews. (4) Online customer reviews cannot mediate the influence of live streaming and price on purchasing decisions. This study adds to the current literature by offering empirical evidence about the mediating role of online customer reviews in the impact of live streaming and pricing on purchasing decision. This study emphasizes the importance of effectively utilizing live streaming features, implementing appropriate pricing strategies, and managing online customer reviews to enhance sales, particularly in the beauty industry.